Comparison of Revision Rates of Non-modular Constrained Versus Posterior Stabilized Total Knee Arthroplasty: A Propensity Score Matched Cohort Study. Issue 1 (February 2017) - Moussa, Mohamed E.; Lee, Yuo-yu; Westrich, Geoffrey H.; Mehta, Nabil; Lyman, Stephen; Marx, Robert G.
Background: Attaining stability during total knee arthroplasty (TKA) is essential for a successful outcome. Although traditional constrained total knee prostheses have generally been used in conjunction with intramedullary stems, some devices have been widely used without the use of stems, referred to as non-modular constrained condylar total knee arthroplasty (NMCCK). Questions/Purposes: The aim of this study was to compare revisions rates after total knee replacement with a non-modular constrained condylar total knee (NMCCK) compared to a posterior-stabilized (PS) design. Methods: Between 2007 and 2012, primary PS total knees were compared with NMCCK implants from the same manufacturer. Propensity score matching was performed, and implant survivorship was examined using a Cox proportional hazards model. The cohort consisted of 817 PS knees and 817 NMCCKs matched for patient demographics, surgeon volume, and pre-operative diagnosis. Results: All cause revisions occurred in 11 of 817 (1.35%) in the PS group compared to 28 of 817 (3.43%) in the NMCCK group ( p  = 0.0168). Excluding revisions for infection and fracture, 8 of 817 (0.98%) PS knees required revision for mechanical failure compared to 18 of 817 (2.20%) NMCCK knees ( p  = 0.0193). Conclusions: While revisions rates in both cohorts were low, there was a significantly higher revision rate with NMCCKs. Given that cases requiring the use of NMCCK implants are likely more complex than those in which PS implants are used, our findings support the judicious use of NMCCK prostheses.